Anti-crisis Communication Competence - I. A. Rumyantseva (Управление)
The article presents the rules of constructive communication that you need to apply in crisis management. These rules are found a lot in common with constructive negotiating techniques. Selected types of communication interactions in a crisis. Using presented in the paper rules, it is proposed that crisis communication competence of executives necessary to successfully manage interactions in the team in today’s economy.